Effects of curcumin on stem-like cells in human esophageal squamous carcinoma cell lines - Almanaa Taghreed N; Geusz Michael E; Jamasbi Roudabeh J (BMC, 2012)
Abstract Background Many cancers contain cell subpopulations that display characteristics of stem cells. Because these cancer stem cells (CSCs) appear to provide resistance to chemo-radiation therapy, development of therapeutic agents that target CSCs is essential. Curcumin is a phytochemical agent that is currently used in clinical trials to test its effectiveness against cancer. However, the effect of curcumin on CSCs is not well established. The current study evaluated curcumin-induced cell death in six cancer cell lines derived from human esophageal squamous cell carcinomas. Moreover, these cell lines and the ones established from cells that survived curcumin treatments were characterized. Methods Cell loss was assayed after TE-1, TE-8, KY-5, KY-10, YES-1, and YES-2 cells were exposed to 20-80 μM curcumin for 30 hrs. Cell lines surviving 40 or 60 μM curcumin were established from these six original lines. The stem cell markers aldehyde dehydrogenase-1A1 (ALDH1A1) and CD44 as well as NF-κB were used to compare CSC-like subpopulations within and among the original lines as well as the curcumin-surviving lines. YES-2 was tested for tumorsphere-forming capabilities. Finally, the surviving lines were treated with 40 and 60 μM curcumin to determine whether their sensitivity was different from the original lines. Results The cell loss after curcumin treatment increased in a dose-dependent manner in all cell lines. The percentage of cells remaining after 60 μM curcumin treatment varied from 10.9% to 36.3% across the six lines. The cell lines were heterogeneous with respect to ALDH1A1, NF-κB and CD44 expression. KY-5 and YES-1 were the least sensitive and had the highest number of stem-like cells whereas TE-1 had the lowest. The curcumin-surviving lines showed a significant loss in the high staining ALDH1A1 and CD44 cell populations. Tumorspheres formed from YES-2 but were small and rare in the YES-2 surviving line. The curcumin-surviving lines showed a small but significant decrease in sensitivity to curcumin when compared with the original lines. Conclusion Our results suggest that curcumin not only eliminates cancer cells but also targets CSCs. Therefore, curcumin may be an effective compound for treating esophageal and possibly other cancers in which CSCs can cause tumor recurrence.